Regulation of co‐ and post‐translational myristoylation of proteins during apoptosis: interplay of N‐myristoyltransferases and caspases. Issue 2 (12th November 2012) - Perinpanayagam, Maneka A.; Beauchamp, Erwan; Martin, Dale D. O.; Sim, Jacky Y. W.; Yap, Megan C.; Berthiaume, Luc G.
Abstract : Myristoylation occurs cotranslationally on nascent proteins and post‐translationally during apoptosis after caspase cleavages expose cryptic myristoylation sites. We demonstrate a drastic change in the myristoylated protein proteome in apoptotic cells, likely as more substrates are revealed by caspases. We show for the first time that both N ‐myristoyltransferases (NMTs) 1 and 2 are cleaved during apoptosis and that the caspase‐3‐ or ‐8‐mediated cleavage of NMT1 at Asp‐72 precedes the cleavage of NMT2 by caspase‐3 mainly at Asp‐25. The cleavage of NMTs did not significantly affect their activity in apoptotic cells until the 8 h time point. However, the cleavage of the predominantly membrane bound NMT1 (64%) removed a polybasic domain stretch and led to a cytosolic relocalization (>55%), whereas predominantly cytosolic NMT2 (62%) relocalized to membranes when cleaved (>80%) after the removal of a negatively charged domain. The interplay between caspases and NMTs during apoptosis is of particular interest since caspases may not only control the rates of substrate production but also their myristoylation rate by regulating the location and perhaps the specificity of NMTs. Since apoptosis is often suppressed in cancer, the reduced caspase activity seen in cancer cells might also explain the higher NMT levels observed in many cancers.—Perinpanayagam, M. A., Beauchamp, E., Martin, D. D. O., Sim, J. Y. W., Yap, M. C., Berthiaume, L. G. Regulation of co‐ and post‐translational myristoylation of proteins during apoptosis: interplay of N ‐myristoyltransferases and caspases. FASEB J. 27, 811–821 (2013). www.fasebj.org